2021
DOI: 10.1177/15347354211006474
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Trismus in Head and Neck Cancer Patients: A Systematic Review of Randomized Controlled Trials

Abstract: Background: Current treatment for head and neck cancers (HNCs) have led to an improved survival. However, the sequelae of cancer treatment often result in trismus, or reduced mouth opening. The purpose of this report is to identify interventional studies for trismus management in HNC patients. Methods: A search of PubMed, Embase, Cumulated Index to Nursing and Allied Health Literature, and the Cochrane Library was conducted in March 2020 for randomized controlled trials (RCTs) involving interventions for trism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
2
14
0
5
Order By: Relevance
“…One study compared therapy through exercises associated with ultrasound and low-intensity PBM and isolated OMT, a configuration similar to the proposal of this series of cases where three patients performed the exercise program exclusively and three the exercises associated with the application of PBM. In synergy with the results of Elgohary et al, it was possible to observe a significant benefit of LASER associated with mouth opening exercises compared to exercise therapy alone [17]. These results deserve an in-depth look as it can be an interesting strategy for the rehabilitation process of these patients and in a shorter period of time.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…One study compared therapy through exercises associated with ultrasound and low-intensity PBM and isolated OMT, a configuration similar to the proposal of this series of cases where three patients performed the exercise program exclusively and three the exercises associated with the application of PBM. In synergy with the results of Elgohary et al, it was possible to observe a significant benefit of LASER associated with mouth opening exercises compared to exercise therapy alone [17]. These results deserve an in-depth look as it can be an interesting strategy for the rehabilitation process of these patients and in a shorter period of time.…”
Section: Discussionsupporting
confidence: 56%
“…Our study observed a reduction in pain levels in all cases, but more markedly in those submitted to the association of exercises with low-frequency LASER. Other studies carried out in similar populations obtained very similar numerical results, with an average reduction of 8 points on the Visual Analogue Scale after the LASER protocol [17,31].…”
Section: Effect Of Laser On Pain Reliefmentioning
confidence: 54%
See 1 more Smart Citation
“…Oral exercise involving actively or passively stretching the jaw using jaw motion rehabilitation systems (e.g., TheraBite, Dynasplin, or tongue depressors) is a potentially helpful approach for preventing or improving trismus. Findings from previous studies [ 13 , 17 , 18 ] provide preliminary support for the efficacy of oral exercise in improving MIO in patients with trismus caused by HNC treatment. However, the sample sizes of the previous studies were small, and there was a high degree of heterogeneity in the oral exercises employed in these studies [ 18 ].…”
Section: Introductionmentioning
confidence: 71%
“…O Questionário MPQ-McGill (11) (The McGill Pain Questionnaire) tem como objetivo estudar a aplicação de indicadores padronizados para a avaliação do impacto da dor na vida de pacientes. Outros autores, como Chee et al (12) , também realizaram estudos objetivando a avaliação da dor na vida de pacientes, utilizando ferramentas, dentre elas, o MPQ-McGill. No Brasil, a versão em português do questionário foi proposta por Pimenta e Teixeira e é denominado Questionário de Dor McGill (Br-MPQ) (13) , que tem sido utilizado em estudos que visam avaliar o impacto da dor orofacial na qualidade de vida de pacientes (14) .…”
Section: Introductionunclassified